Gamers Acceptance of Nintendo's Ring Fit as Exergaming and Gamified Learning Tool - Tony Wibowo; Encik Mohammad Habib Tara; Farrel Ardhatama; Li Cen (CV. Media Inti Teknologi, 2025)
Background: Obesity continues to be a worldwide issue, worsened by sedentary lifestyles and excessive screen exposure. Exergames, which merge physical activity with interactive gaming, offer a creative approach to encouraging fitness and education. Nintendo’s Ring Fit Adventure combines movement-based gameplay with goal-driven challenges that enhance motivation, engagement, and aspects of self-regulated learning (SRL).Aims: This study investigated how Ring Fit Adventure is accepted as both an exergame and a gamified educational tool, highlighting its contribution to fostering self-regulated learning (SRL) behaviors such as setting goals, self-monitoring, and reflection. This study utilized the Technology Acceptance Model (TAM) alongside the DeLone and McLean Information Systems Success Model (D&M) to determine the factors that affect users' perceptions and intentions.Methods: An experimental qualitative study was conducted with 50 students from Universitas Internasional Batam, who were intentionally selected. The participants played Ring Fit Adventure for 30 minutes and were then interviewed using TAM and D&M frameworks. Data collected from observations and interviews were descriptively analyzed to assess perceived usefulness, ease of use, system quality, satisfaction, and behaviors related to self-regulated learning (SRL).Results: Results showed that the participants found Ring Fit to be engaging, user-friendly, and motivating. The game's feedback mechanism and adaptable challenges promote self-regulation by encouraging goal setting and performance tracking. Minor issues with the sensors did not significantly affect user satisfaction.Conclusion: Ring Fit Adventure successfully combines fitness, entertainment, and self-directed learning aspects. By promoting independence, introspection, and ongoing involvement, exergaming has the potential to improve both physical well-being and the intrinsic drive for lifelong learning.